Inflammation and Physical Performance in Overweight and Obese Schoolchildren - Cristina Popescu; Daniela Matei; Anca Maria Amzolini; Magdalena Rodica Trăistaru (Life)
Obesity represents a critical public health concern, often linked to low-grade chronic inflammation starting in childhood. This study aimed to evaluate the impact of a 12-week kinesiotherapy program on physical performance and levels of leptin and C-reactive protein (CRP) in overweight and obese children. Methods: Conducted at the Filantropia Municipal Clinical Hospital, 160 children aged 6 to 15 were randomly assigned to a study group (SG, n = 80) and a control group (CG, n = 80). The SG engaged in a tailored kinesiotherapy program, while the CG maintained their usual activities. All children and their families learned five key principles for preventing and managing obesity. Results: Results indicated significant improvements in the SG, with enhancements in the 6 min walking distance, Timed Up and Go test, and walking cadence (all p-values < 0.001). Notably, leptin and CRP levels (23.02 ± 7.17 to 16.62 ± 7.83, 4.13 ± 1.00 to 3.90 ± 0.95 mg/l, respectively) decreased significantly in the SG, contrasting with no significant changes in the CG. Regression analysis revealed a positive correlation between leptin levels and physical activity in the SG (coefficient: 0.5642, R-squared: 0.266). Conclusions: These findings suggest that targeted exercise programs can effectively enhance physical performance and reduce inflammation markers in overweight children, highlighting the importance of tailored interventions in managing obesity.